Development of Brady-Tachy heart automotive monitoring (BT-Heartomotive) device to prevent motor-vehicle accident - Mohd Azrul Hisham, Mohd Adib; Muhamad Hazim, Khalili; Nur Hazreen, Mohd Hasni (Centre for Advanced Research on Energy (CARe), 2019)
The rate of car accidents is worrying nowadays. Other than problems in driving attitudes and skills, road accidents are also caused by uncontrollable factors such as medical conditions and drowsiness. These factors can be avoided by having early detection. The BT-Heartomotive device is a device that can detect early signs of drowsiness and health problems by measuring the heart rate of the drivers. Heart rate measurement can reveal a lot about the physical conditions of an individual. BT-Heartomotive device consists of three main components: the sensor, microcontroller, and heart rate monitor.